2022
DOI: 10.7554/elife.73837
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis SAC9 enzyme is enriched in a cortical population of early endosomes and restricts PI(4,5)P2 at the plasma membrane

Abstract: Membrane lipids, and especially phosphoinositides, are differentially enriched within the eukaryotic endomembrane system. This generates a landmark code by modulating the properties of each membrane. Phosphatidylinositol 4,5-bisphosphate [PI(4,5)P2] specifically accumulates at the plasma membrane in yeast, animal, and plant cells, where it regulates a wide range of cellular processes including endocytic trafficking. However, the functional consequences of mispatterning PI(4,5)P2 in plants are unknown. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 97 publications
2
24
0
Order By: Relevance
“…To identify the molecular processes leading to exclusion of PI(4,5)P 2 from the leading zone in late cytokinesis, we followed the subcellular localization of the plant-specific enzyme SAC9 which participates in the depletion of PI(4,5)P 2 at the plasma membrane during endocytosis ( 11 ). We observed that mCit-SAC9 is enriched at the phragmoplast leading zone (index > 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…To identify the molecular processes leading to exclusion of PI(4,5)P 2 from the leading zone in late cytokinesis, we followed the subcellular localization of the plant-specific enzyme SAC9 which participates in the depletion of PI(4,5)P 2 at the plasma membrane during endocytosis ( 11 ). We observed that mCit-SAC9 is enriched at the phragmoplast leading zone (index > 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2a to 2c, yellow arrow, Extended Data 4, 5), suggesting a role of SAC9 in PI(4,5)P 2 depletion at the leading zone. To test this hypothesis, we analyzed the localization of a catalytically inactive variant of SAC9 (tdTOM-SAC9 C459A ), for which the signal in the cytoplasm is reduced compared with mCIT-SAC9, allowing imaging at higher resolution ( 11 ). Like mCit-SAC9, tdTOM-SAC9 C459A is enriched at the leading zone while PI(4,5)P 2 is depleted, leading to a clear mutual exclusion between the enzyme and its substrate along the cell plate (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations